Acupuncture therapy for breast cancer‐related lymphedema: A systematic review and meta‐analysis. Issue 12 (13th October 2019) - Hou, Wenzhen; Pei, Lixia; Song, Yafang; Wu, Jian; Geng, Hao; Chen, Lu; Wang, Yuhang; Hu, Yao; Zhou, Jinyong; Sun, Jianhua
Abstract: This study aimed to conduct a comprehensive analysis of clinical studies on acupuncture treatment for breast cancer‐related lymphedema (BCRL), so as to explore the efficacy and safety of acupuncture treatment and provide evidence for the clinical decision‐making. Public databases, mainly including China Academic Journals Full‐text Database, Database of Chinese Sci‐Tech Journal, Wanfang, PubMed, Embase and the Cochrane Library, from the establishment of databases to December 2018 were searched for randomized controlled trials (RCT) of acupuncture for BCRL. Clinical RCT on the treatment of BCRL with acupuncture combined with drugs or functional exercise were enrolled for the analysis. Bias risk and quality were assessed by two investigators according to the Cochrane Handbook 5.1.0 standard, and the Revman 5.3 software was used for meta‐analysis. A total of 13 studies were enrolled, comprising 747 patients (377 in the treatment group and 370 in the control group). The results of meta‐analysis showed that acupuncture intervention could improve the total effective rate for the treatment of BCRL (odds ratio = 4.62; 95% confidence interval 2.61–8.17). Recent studies suggest that acupuncture therapy can alleviate the upper limb swelling and improve the subjective pain and discomfort in patients with BCRL, regardless of the control intervention used. However, the number of high‐quality RCT is low. Moreover, most of the studies adopted inconsistent efficacy indicators. Hence, additional blinded, large‐sample, randomized, well‐controlled studies with objective and uniform efficacy indicators are needed, especially in China, to confirm the findings.